«THE ODD MAN OUT»: PAGES FROM THE DIARY OF THE HIGH SCHOOL STUDENT IN THE 1870s. THROUGH THE EYES OF A MODERN HISTORIAN - Sergei Dudarev (Гуманитарные и юридические исследования)
The article focuses on the work by G.-M. Amirov «Among the Mountaineers of Northern Dagestan» (from the diary of a schoolboy), which is a representative example of the perception by educated person from the mountain environment of the views, customs, traditions, etc. of his society with the eyes of a person who has familiarized himself with European (Russian) culture. The analysis of the historical source undertaken by the author represents a research attempt to elucidate the ideas about the mountainous world of the educated highlander, that is, to study the view of the community from within. The research was carried out in the imagological key, in which the perceiving subject himself, is the bearer of national self-consciousness, and his own value system, changed by European education, simultaneously. G.-M. Amirov provides valuable information on certain socio-cultural stereotypes of mountain people, through the prism of which they, in turn, looked at the person who was the representative of "Inomir" (Another world) to them. The author of this article, based on the observations of G.-M.Amirov and the experience of other authors of the nineteenth and early 21st centuries (both mountainous and Russian), seeks to show the criteria of «own» and «foreign» for Dagestanian mountaineers in the early 1870s, as well as their moral, religious and psychological assessment in patriarchal-traditional environment.